High levels of anti‐Nef antibodies may prevent AIDS disease progression in vertically HIV‐1‐infected infants. Issue 2 (14th February 2014) - Corró, Guillermo; Crudeli, Cintia Milena; Rocco, Carlos Alberto; Marino, Silvia Alejandra; Sen, Luisa
Abstract : Introduction: HIV‐1‐associated CD4+ T‐cell depletion is a consequence of uninfected cell death. Nef is one of the viral factors that trigger apoptosis on bystander cells, though the plasma Nef levels do not correlate with Th lymphocytes counts. The aim of our study was to evaluate whether anti‐Nef antibodies were involved in paediatric AIDS development and whether they can prevent the CD4+ T‐cell depletion in vertically infected children. Methods: Two hundred and seventy three HIV‐1 vertically infected children seen at Garrahan Paediatric Hospital were randomly included in the study, adding 13 selected cases: seven LTNP (long‐term non‐progressors) and six RP (rapid progressors) children ( n total =286). Specific anti‐HIV‐1‐Nef antibodies were titrated by indirect ELISA and compared between groups. The plasma blocking effect on Nef‐dependent cytotoxicity was evaluated in Jurkat cells using recombinant Nef as apoptotic stimulus and patient plasmas as blockers, measuring the apoptotic levels using Annexin‐V stain and flow cytometry. Results: Only 63.4% of the patients had specific anti‐Nef antibodies, and the levels of anti‐Nef antibodies found in the selected LTNPs plasmas were always significantly higher ( p =1.55×10 −4 ) than those in RPs or general HIV‐1+ paediatric populations. The LTNPs' plasma had a strong inhibitory effect on Nef‐dependent cytotoxicity even at high dilutions, while RP plasmas had little or no effect on Nef‐induced apoptosis. Discussion and conclusions: High anti‐Nef antibody levels are associated and predict slow or non‐progression to AIDS in vertically HIV‐1‐infected children. They could be an efficient tool in preventing Nef‐associated bystander effect, preserving CD4+ T‐cells and the immune function in the context of paediatric HIV‐1 infection.